The confidence of wildflowers - Smeltzer, Micalea (Page & Vine., 2022)
"My future is a big 'what if' at the moment and I'm fine with that. For the most part. When Thayer Holmes moves in next door, the grumpy landscaper both fascinates and amuses me. When he asks me to nanny his kid, it's a great way to make some extra money. It's impossible not to fall in love with Thayer and his adorable son. There's a big problem though. I'm eighteen. He's thirty-one. Falling for someone almost fifteen years older than me wasn't part of my plans, but sometimes things happen when you least expect them" -- From the back cover
Keywords: Romance -- Fiction; Man-woman relationships -- Fiction